Síntese e caracterização de combustíveis nucleares metálicos do tipo U-Zr-Mo-Gd - Longen, Fabio Rogerio (2013)
The main objective of this study was to supply information to establish a long term strategy for metallic nuclear fuel manufacture based on γ-U(Zr, M ) alloys where M = transition metal or rare-earth for compact PWR-type nuclear reactors. The present study investigated the phase stability in the U-Zr-Mo and U-Zr-Gd ternary systems, varying the zirconium or molybdenum concentration and zirconium or gadolinium concentration, respectively For this, U1-X(Zr1-YM Y)X metallic alloys (with X = 35 - 70 wt.% and Y = 3 13 wt.%) were melted in arc-furnace and heat treated at 950oC for 15 h, in an argon atmosphere. At the end of each heat treatment, the annealed samples were quenched in water at room temperature. After each preparation step, the alloys prepared were characterized by X-ray diffraction to identify the crystalline phases, and by optical microscopy, to determine the resulting microstructure. The U-Zr-Gd alloys were also characterized by Mössbauer spectroscopy. The results showed that the as-melted U-Zr-Mo samples solidified mostly in the γ-U(Zr, Mo) phase and had a very homogeneous microstructure. The uranium richest sample was the exception, which precipitated the α-U(Zr, Mo) phase besides the γ-U(Zr, Mo) phase. It was further verified that heat treatments followed by quenching promoted the partial decomposition of the γ phase in the δ and α phases, in amounts that depend on X. However, for the alloys of the U-Zr-Gd system, the results showed that the samples solidified mostly in the δ-U(Zr, Gd)2 phase. The uranium richest sample revealed a single crystalline phase, and was the first monophasic alloy of the U-Zr-Gd obtained to date.